2014
DOI: 10.1186/1472-6963-14-297
|View full text |Cite
|
Sign up to set email alerts
|

Networking between community health programs: a team-work approach to improving health service provision

Abstract: BackgroundNetworking between non-government organisations in the health sector is recognised as an effective method of improving service delivery. The Uttarakhand Cluster was established in 2008 as a collaboration of community health programs in rural north India with the aim of building capacity, increasing visibility and improving linkages with the government. This qualitative research, conducted between 2011-2012, examined the factors contributing to formation and sustainability of this clustering approach.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Several published case studies have indicated the importance of common identity or faith in network development. 19,20 In Uttarakhand, North India, one of the authors analysed the genesis of a network between faith-based health and develop-ment organisations. 19 A "broadly similar faith understanding" was identified as being the most significant factor determining the "ties" that bound members in the network.…”
Section: Establishing Can Domentioning
confidence: 99%
“…Several published case studies have indicated the importance of common identity or faith in network development. 19,20 In Uttarakhand, North India, one of the authors analysed the genesis of a network between faith-based health and develop-ment organisations. 19 A "broadly similar faith understanding" was identified as being the most significant factor determining the "ties" that bound members in the network.…”
Section: Establishing Can Domentioning
confidence: 99%
“…1 To counteract this weakness in global health, there is growing evidence that networking and intentional collaboration between community health programs can improve service delivery and promote greater impact. 2,3 A number of terms are used in the literature to describe the ways community health programs can work together. Agranoff and McGuire define networks as "the process of facilitating and operating in multi-organisational arrangements to solve problems that cannot be solved, or easily solved, by a single organisation."…”
Section: Introductionmentioning
confidence: 99%
“…doi: 10.7243/2055-7205-6-1 information or goods or implementing joint activities, in such a way that individual (or organisational) autonomy remains intact" [2]. Collaborating on a voluntary basis is the essence of networking activities, and creating a network allows its members to join their efforts and benefit from their partnership [3]. The goals of a network are major determinants of that network's characteristics.…”
mentioning
confidence: 99%
“…The goals of a network are major determinants of that network's characteristics. The membership criteria, the structure of the collaboration, and the funding of the network will all depend on what the network is aiming at [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation